2020
DOI: 10.1002/jppr.1695
|View full text |Cite
|
Sign up to set email alerts
|

Optimising health outcomes via pharmacist delivered telehealth medicines management: a systematic review

Abstract: Background: Pharmacist-led telehealth is an innovative service delivery model that may provide an alternative mode of care. It remains unclear how surrogate markers of health conditions differ when pharmacist services are delivered via telehealth compared to usual care. Aims: To assess if pharmacist-led telehealth interventions alter surrogate markers of health conditions. Methods: Pharmacist-led telehealth interventions compared to another active intervention for people using one or more regular medicines wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…It consists of a variety of electronic communication methods and digital tools to allow healthcare workers to interact with patients “remotely” [ 20 22 ]. Video and audio media, sometimes accompanied by web- or app-based interfaces, both synchronous and asynchronous, are common modalities through which telemedicine can be provided [ 23 , 24 ]. Similar to most other telemedicine subclasses, telepharmacy is getting more attention during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…It consists of a variety of electronic communication methods and digital tools to allow healthcare workers to interact with patients “remotely” [ 20 22 ]. Video and audio media, sometimes accompanied by web- or app-based interfaces, both synchronous and asynchronous, are common modalities through which telemedicine can be provided [ 23 , 24 ]. Similar to most other telemedicine subclasses, telepharmacy is getting more attention during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic crisis has affected patients currently residing at a distance from a remotely located hospital, pharmacy or healthcare centre, or being requested to be in quarantine, which has increased the need for telepharmacy 11. It has been reported that pharmacist-led telehealth services using ICT were at least as effective as face-to-face services, and reduced potential side effects and hospital admissions in outpatient populations with chronic diseases especially where usual care could not be provided 12–14. Therefore, this study aims to analyse the effect of a telepharmacy service involving a customised mobile device in comparison with the usual pharmacist service on the humanistic and clinical outcomes of patients with RA (the PROUD trial).…”
Section: Introductionmentioning
confidence: 99%